Valvuloplasty Without Prosthetic Ring or Band in Patients with Degenerative Mitral Regurgitation: Long-Term Results and Predictive Factors for Outcomes - Kalil,Renato A. K. (2021)
Abstract Introduction: Mitral valvuloplasty including ring/band support is widely performed despite potential drawbacks of rings. Unsupported valvuloplasty is performed in only a few centers. This study aimed to report long-term outcomes of patients undergoing unsupported valvuloplasty for degenerative mitral regurgitation (MR) and to identify predictive factors for outcomes. Methods: This is a retrospective cohort including patients undergoing mitral valve repair for degenerative MR from 2000 to 2018. The main techniques were Wooler annuloplasty and quadrangular resection. Kaplan-Meier curves and Cox regression models were used for statistical analysis. Results: One hundred fifty-eight patients were included (median age: 64.0 years). In-hospital mortality was 2.5%. Maximum follow-up was 19.6 years, with a median of 4.7 years (992 patient-years). Overall survival at 5, 10, and 15 years was 91.0% (95% confidence interval [CI]: 85.7-96.3), 87.6% (95% CI: 80.7-94.5), and 78.1% (95% CI: 65.9-90.3), respectively. The European System for Cardiac Operative Risk Evaluation (EuroSCORE) II was an independent predictor of late death (hazard ratio [HR] 1.42; P=0.016). Freedom from mitral reoperation at 5, 10, and 15 years was 88.1% (95% CI: 82.0-94.2), 82.4% (95% CI: 74.6-90.2), and 75.7% (95% CI: 64.1-87.3), respectively. Left atrial diameter > 56 mm was associated with late reintervention in univariate analysis (HR 1.06; P=0.049). Conclusion: Degenerative MR can be successfully treated with repair techniques without annular support, thus avoiding the technical and logistical drawbacks of ring/band implantation while maintaining good long-term results. EuroSCORE II was a risk factor for late death, and larger left atrium was associated with late reoperation.